Effects of different land use change on temperate seminatural grasslands - Czóbel, Szilárd (Acta Biologica Szegediensis, 2005)
The specific objectives of this study were to determine the effects of different land use changes (extensive grazing, fertilization and irrigation) on the botanical and soil parameters, plant biomass production and CO2 gas exchanges and to provide data for model development. Experimental work has been carried out for 3 years in two characteristic semi-natural temperate grassland type of Hungary. Small grassland plots were positioned along two transects at fertilized and irrigated sites of loess steppe. At the fertilized (Isaszeg) site, mineral fertiliser was applied once a year at the beginning of the vegetation period, while top spray irrigation was operated continuously during each vegetation period at the irrigated site (Gödöllő). On the plain site an area of 6 ha of dry sand grassland was fenced off from the extensively grazing cattle herd. The shortest response of land-use change can be observed at botanical composition and partly at NEE (CO2), whereas soil parameters are significantly affected at longer time-scale. The observed changes were strongly correlated to climatic conditions, emphasized the importance of the water regime.